Analysis of Existing Empirical Research Methods for Studying (Online) Privacy and Surveillance - Sevignani, Sebastian; Kreilinger, Verena; Allmer, Thomas; Fuchs, Christian

X-ray absorption near-edge spectroscopy investigation of the oxidation state of Pd species in nanoporous SnO2 gas sensors for methane detection - Wagner, T.; Bauer, M.; Sauerwald, T.; Kohl, C.-D.; Tiemann, Michael (Thin Solid Films)
We report the correlation of the aging of Pd-doped SnO2 methane sensors with the change of the oxidation state of Pd. Mesoporous SnO2 doped with palladium species was prepared and exposed to different gas mixtures at high temperature (600 °C) to simulate long term usage. After each exposure step a fraction of the sample was cooled down to “freeze” the current oxidation state of Pd which was then analyzed by X-ray Absorption Near-Edge Spectroscopy (XANES) using the 'white line' (i.e. the absorption peak corresponding to the transition from the 2p3/2 core level to unoccupied 4 d states) intensity of the L(III) edge as a probe for the oxidation state. The Pd oxidation state correlates with the response of the resistive SnO2 sensor to methane gas, as determined by measuring the gas response to different concentrations of methane. Samples treated with 5000 ppm methane in air show a significant reduction of Pd(II) to Pd(0), depending clearly on the carrier gas (synthetic air, pure nitrogen) and on the temperature (600 °C vs. 300 °C).

A High Temperature Capacitive Humidity Sensor Based on Mesoporous Silica - Wagner, Thorsten; Krotzky, Sören; Weiß, Alexander; Sauerwald, Tilman; Kohl, Claus-Dieter; Roggenbuck, Jan; Tiemann, Michael (Sensors)
Capacitive sensors are the most commonly used devices for the detection of humidity because they are inexpensive and the detection mechanism is very specific for humidity. However, especially for industrial processes, there is a lack of dielectrics that are stable at high temperature (>200 °C) and under harsh conditions. We present a capacitive sensor based on mesoporous silica as the dielectric in a simple sensor design based on pressed silica pellets. Investigation of the structural stability of the porous silica under simulated operating conditions as well as the influence of the pellet production will be shown. Impedance measurements demonstrate the utility of the sensor at both low (90 °C) and high (up to 210 °C) operating temperatures.

Micrometer-sized nanoporous tin dioxide spheres for gas sensing - Smått, J.-H.; Lindén, M.; Wagner, T.; Kohl, C.-D.; Tiemann, Michael (Sensors and Actuators B: Chemical)
We report the synthesis of mesoporous tin dioxide (SnO2) materials with well-defined particle morphology. The products consist of uniform spheres with a diameter of 5 μm. The spheres are hierarchically porous with two distinct pore modes of 5.0 nm and 52 nm, respectively. This special porosity is the result of a synthesis procedure which involves a ‘hard templating’ (nanocasting) process. The product forms an approximately homogeneous monolayer of spheres on a sensor substrate and shows promising response to methane gas with low cross-sensitivity to water. The structural properties and gas-sensing performance are compared with a mesoporous SnO2 material without defined morphology, prepared by a ‘soft templating’ procedure.

Photocatalytic ozone sensor based on mesoporous indium oxide: Influence of the relative humidity on the sensing performance - Wagner, T.; Hennemann, J.; Kohl, C.-D.; Tiemann, Michael (Thin Solid Films)
Mesoporous In2O3, synthesized by a nanocasting procedure, is used as a resistive gas sensor for ozone in very low concentrations (from 20 ppb to 2.4 ppm) at room temperature. Its sensing performance is substantially increased by illumination with blue light (460 nm, 2.7 eV). For low ozone concentrations the sensor response increases with increasing humidity. However, higher humidity also results in the occurrence of a saturation of the response at lower ozone concentrations; this is rationalized by assuming a poisoning of surface active sites by hydroxyl groups.

A Critical Contribution to Theoretical Foundations of Privacy Studies - Allmer, Thomas (Journal of Information, Communication & Ethics in Society)

Piezoelectric sensor array with evaluation electronic for counting grains in seed drills - Meyer zu Hoberge, S.; Hilleringmann, Ulrich; Jochheim, C.; Liebich, M. (IEEE Africon '11)

Die Rezeption der Kirchenmusik Anton Bruckners. Genese, Tradition und Instrumentalisierung des Vergleichs mit Giovanni Pierluigi da Palestrina - Höink, Dominik
Einen 'modernen Palestrina' nennt Max Auer den Komponisten Anton Bruckner und pointiert damit eine noch heute virulente Vorstellung, die den katholisch-frommen Bruckner auf einer Linie mit dem durch die Retterlegende glorifizierten und päpstlicherseits kanonisierten Ideal Giovanni Pierluigi da Palestrina sieht. Diese stil- und rezeptionsgeschichtliche Untersuchung richtet aus diachroner Perspektive den Blick auf Genese und Tradierung dieses Komponistenvergleichs vom 19. Jahrhundert bis in die Gegenwart. Im Zentrum steht dabei die Analyse des maßgeblichen wissenschaftlichen Bruckner-Schrifttums und seiner kontextuellen Verortung innerhalb der bisweilen höchst ideologisch aufgeladenen musikgeschichtlichen Diskurse. Ferner werden auf der Basis neuer Quellen die Kanonisierungsbestrebungen hochrangiger Vertreter der Bruckner-Gesellschaft im Rahmen der sogenannten 'Aktion Rom' ausgewertet, die für die Instrumentalisierung des Vergleichs von zentraler Bedeutung sind. Es folgt eine Analyse derjenigen Kompositionen, die in die Nähe des Palestrina-Stils gerückt wurden. Am Ende der Arbeit steht eine Neubewertung des Vergleichs auf der Grundlage der aus Rezeptionsgeschichte und Analyse gewonnenen Ergebnisse.

Injection currents in (110)-oriented GaAs/AlGaAs quantum wells: recent progress in theory and experiment - Duc, H. T.; Pochwala, M.; Förstner, Jens; Meier, Torsten; Priyadarshi, S.; Racu, A. M.; Pierz, K.; Siegner, U.; Bieler, M. (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XV)
We experimentally and theoretically investigate injection currents generated by femtosecond single-color circularly-polarized laser pulses in (110)-oriented GaAs quantum wells. The current measurements are performed by detecting the emitted Terahertz radiation at room temperature. The microscopic theory is based on a 14 x 14 k • p band-structure calculation in combination with the multi-subband semiconductor Bloch equations. For symmetric GaAs quantum wells grown in (110) direction, an oscillatory dependence of the injection currents on the exciting photon energy is obtained. The results of the microscopic theory are in good agreement with the measurements.
Keywords: tet_topic_qw

Electron g-factor anisotropy in symmetric (110)-oriented GaAs quantum wells - Hübner, J.; Kunz, S.; Oertel, S.; Schuh, D.; Pochwała, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten; Oestreich, M. (Physical Review B)
We demonstrate by spin quantum beat spectroscopy that in undoped symmetric (110)-oriented GaAs/AlGaAs single quantum wells, even a symmetric spatial envelope wave function gives rise to an asymmetric in-plane electron Land´e g-factor. The anisotropy is neither a direct consequence of the asymmetric in-plane Dresselhaus splitting nor a direct consequence of the asymmetric Zeeman splitting of the hole bands, but rather it is a pure higher-order effect that exists as well for diamond-type lattices. The measurements for various well widths are very well described within 14 × 14 band k·p theory and illustrate that the electron spin is an excellent meter variable for mapping out the internal—otherwise hidden—symmetries in two-dimensional systems. Fourth-order perturbation theory yields an analytical expression for the strength of the g-factor anisotropy, providing a qualitative understanding of the observed effects.
Keywords: tet_topic_qw